Healing the inner city child : creative arts therapies with at-risk youth - Camilleri, Vanessa A., 1973- (Jessica Kingsley Publishers, 2007)
Healing the Inner City Child presents a diverse collection of creative arts therapies approaches to meeting the specific mental health needs of inner city children, who are disproportionately likely to experience violence, crime and family pressures and are at risk of depression and behavioural disorders as a result. The contributors draw on their professional experience in school and community settings to describe a wide variety of suitable therapeutic interventions, including music, play and art therapy as well as psychodrama and dance/movement approaches, that enable children to deal with e.